How to plot a payback [large type] - Ferguson, Melissa, 1985- (Center Point Large Print, 2024)
"Successful screenwriter Finn Masters just landed his dream job writing for Neighbors, one of Hollywood's highest-rated, longest-running sitcoms. The only downside? It will put him back in proximity of the show's universally adored, optimistic, altruistic star, Lavender Rhodes, who has been inadvertently ruining his life since they were school chums in England. But she doesn't even know she destroyed his acting career and wrecked his relationship with the love of his life. He's not about to let this woman yank yet another dream out from under his feet. In fact, he realizes he's been given the ideal opportunity to plot his payback: spinning her character in shocking new directions. What could go wrong? Only everything. As Finn's not-so-brilliant plot backfires one scene after the next, catching him in the blasts, he's forced to think about this impossible, infuriating . . . and maybe even lovable woman in an entirely new light."--